Spotlight on brodalumab in the treatment of moderate-to-severe plaque psoriasis: design, development, and potential place in therapy - Roman M; Chiu MW (Dove Medical Press, 2017)
Michael Roman,1 Melvin W Chiu2 1David Geffen School of Medicine at UCLA, 2Division of Dermatology, David Geffen School of Medicine at UCLA, Los Angeles, CA, USA Abstract: Brodalumab is a novel fully human immunoglobulin G2 monoclonal antibody that antagonizes the interleukin (IL)-17 pathway by binding with high affinity to human IL-17RA. The role of IL-17A in the pathogenesis of psoriasis, as well as the remarkable effectiveness of IL-17 inhibitors in the treatment of moderate-to-severe plaque psoriasis, is well established. The mechanism of action of brodalumab is unique in that it inhibits the IL-17 receptor compared to the two other currently FDA-approved IL-17 inhibitors, secukinumab and ixekizumab, which inhibit the IL-17A molecule itself. The efficacy of brodalumab in the treatment of moderate-to-severe plaque psoriasis has been demonstrated in phase 2 and 3 trials, and subsequently the FDA approved this medication in February 2017. Brodalumab was approved in Japan in July 2016 and approval is pending in Europe. The safety and adverse effects of brodalumab were reviewed across several clinical trials, which, similar to other IL-17 inhibitors, demonstrated increased rates of neutropenia and Candida infections. Brodalumab treatment, similar to ixekizumab and secukinumab, showed no improvement in inflammatory bowel disease patients, and on the contrary, more exacerbations were encountered. Suicidal ideation and behavior events have been reported with brodalumab treatment and are of significant concern. Brodalumab provides another highly effective treatment option for moderate-to-severe plaque psoriasis. Keywords: brodalumab, biologics, IL-17, plaque psoriasis